If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2 + -3x) = x + -14 (2 * 5 + -3x * 5) = x + -14 (10 + -15x) = x + -14 Reorder the terms: 10 + -15x = -14 + x Solving 10 + -15x = -14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + -15x + -1x = -14 + x + -1x Combine like terms: -15x + -1x = -16x 10 + -16x = -14 + x + -1x Combine like terms: x + -1x = 0 10 + -16x = -14 + 0 10 + -16x = -14 Add '-10' to each side of the equation. 10 + -10 + -16x = -14 + -10 Combine like terms: 10 + -10 = 0 0 + -16x = -14 + -10 -16x = -14 + -10 Combine like terms: -14 + -10 = -24 -16x = -24 Divide each side by '-16'. x = 1.5 Simplifying x = 1.5
| ax-b=ac-b | | 4x=8a | | X+900=724+1448 | | -0.48+0.15y=-0.384 | | x=5x+5+3x | | 5(5y-2)+12+2(4y+4)=10 | | (2x+10)+(x-12)=180 | | 4b-2b=26 | | y/4=8/11 | | 2x+3(x-4)=23 | | 8(z+8)-3=-7(z-2) | | 1X*2R= | | 35(x-140)=70 | | 4x-2=15-3x | | -5(v+1)+1=4(v+4) | | 5/6x-1/=2 | | -3x-17=19x-6 | | logx=0.3010 | | x-1/2-x-2/3=1/2 | | 4-6/18-14 | | y2-y1/x2-x1= | | (5-x)(1+x)=0 | | m^2+2m+4= | | -2yx^2+y^2=25 | | 3x-1/4=4x-1/3 | | (4sin^2(x))-4cosx+1=0 | | 8(7m+8)=y | | 2(3x-7)-(6-x)=4-(x-5) | | 25(2x-1)=6(x+3)+3x | | v=4/3Π×9^ | | Z/1.6=1.1 | | 4x^3+2x^2+0.25x=0.173 |